Analisis Sensitivitas terhadap Metode WP dan VIKOR dalam Pengambilan Keputusan Penentuan Penerima Beasiswa di UNJ - Ghefira Nur Kahfi; Sudarwanto; Siti Rohmah Rohimah (Program Studi Matematika Universitas Negeri Jakarta, 2022)
Kartu Jakarta Mahasiswa Unggul (KJMU) is one of the scholarship programs available at UNJ and is funded by the DKI Jakarta Regional Budget. The recipients increase every year but the costs incurred remain so that a proper Sistem Penerimaan Keputusan (SPK) is needed. One of the SPK methods is the Weighted Product Model (WPM) and Viˇse Kriterijumska Optimazajica I Kompromiso Resenje method (VIKOR). The WP method begins by calculating the weight of each criterion and then ranking it. Meanwhile, the VIKOR ranking method is seen based on compromise solutions. Next, a sensitivity test was conducted to see how sensitive the two methods were to changes that occurred. This research was conducted 3 times and obtained an average percentage change in ranking results of 16,776 % for the WP method and 18,156 % for the VIKOR method, so that the VIKOR method is more appropriate to be applied in the KJMU scholarship acceptance decision system at UNJ.